The small-scale forward modeling method for large models based on the wave equation. (2nd December 2015) - Pu, Yitao; Yin, Xingyao; Cao, Danping; Zhang, Chong
Abstract: The small-scale modeling of an underground geological model can avoid the equivalent large-scale assumptions and show the seismic reflection characteristics more precisely. Considering the large number of perfectly matched layer (PML) boundaries in small-scale modeling of large models, we analyze the absorption effect of the PML boundary in different spatial spacing, and apply variable-grid technology to small-scale seismic modeling. Using small grids to compute the model region and large grids to compute the PML boundary, we successfully reduce the amount of PML boundary layers in small-scale seismic modeling. This method can reduce data storage and improve computational efficiency dramatically.